The Role of Optimism and Psychosocial Factors in Athletes Recovery From ACL Injury: A Longitudinal Study - Williams, Tom; Evans, Lynne; Robertson, Angus; Hardy, Lew; Roy, Stuart; Lewis, Daniel; Glendinning, Freya (Frontiers in Sports and Active Living, 2020)
Despite a growing interest into the role of psychosocial factors during the recovery period following sports injuries, there remains a paucity of longitudinal studies examining the indirect relationships between psychosocial factors, psychological responses, and recovery outcomes. The purpose of this study was to construct and test a conceptual model which examined the indirect relationships between psychosocial factors, rehabilitation adherence, and perceived knee function up to 12 months post anterior cruciate ligament (ACL) surgery. A prospective, longitudinal, and repeated measures design was employed, wherein 81 injured athletes (Mage 26.89, SD = 7.52) completed measures of psychosocial factors, rehabilitation adherence, and perceived knee function on seven occasions (pre-surgery to 1 year post-surgery). Bayesian structural equation modeling evaluated the hypothesized indirect relationships proposed within the conceptual model. The main findings from this study was empirical support for a time-ordered, conceptual model which demonstrated that pre-surgery optimism had a significant overall indirect effect on perceived knee function at 12 months post-surgery (sum of indirect; αβ = .08, post. SD = .05, CI [.01, .04]), as well as a specific indirect effect through secondary appraisal at 1 month post-surgery, efficacy at 2 months post-surgery, and rehabilitation adherence at 6 months post-surgery (αβ = .03, post. SD = .03, CI [.00, .10]). Collectively, this study provides support for a number of previously hypothesized, but not empirically examined, indirect relationships between psychosocial factors and recovery outcomes, In doing so, we provide a conceptual model which has the potential to help guide individualised treatment recommendations, as well as identify individuals at risk of compromised recovery outcomes following ACL surgery.